PENGARUH DUKUNGAN TOP MANAJEMEN, BUDAYA LAYANAN, DAN ORIENTASI PELAYANAN DALAM KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN - Andreas Wahyu Gunawan; Mira Ferisca Beyer (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2012)
The purpose of this paper is to examine whether there is a relationship between variable stop management support, service culture and service orientation. Where is the service culture is antecedent of service orientation. This case, was also examined the relationship between service orientation, service quality, customer satisfaction and customer loyalty in starbucks coffee cibubur square, cibubur junction, bogor rest area, botani square, and university of indonesia. In this study, data were collected through surveys and structural equation modeling is used for data analysis. The number of samples as many as 100employees and 100 customers starbucks coffee that is divided in cibubur square, cibubur junction, bogor rest area, botani square, and university of indonesia and 100 customers of Starbucks Coffee. Factor analysis with SPSS and structural equation model with AMOS program used to test the hypothesis.The results of this study indicate that the support of top management, the service culture was positively related to service orientation and service quality. However, the service quality to customer satisfaction found a negative relationship.Then between customer satisfaction and customer loyalty is strong and positively related to each other.Keywords : Services, Organizational culture, Service quality, Satisfaction, Loyalty.